Comparison of Influences of Superheat Degree on R32 and R22 Rolling Piston Compressor Refrigeration System - Wang Chao; Tao Leren; Wu Chao; Yang Lihui; Li Qingpu; Yu Zhongyang (Zhileng xuebao)
The influences of superheat degree on R22 and R32 refrigeration system’s performances are studied experimentally with variable frequency rolling piston compressor refrigeration loop test bench. With the quantitative analysis, some change trends of R32 refrigeration system under the superheat condition are summarized, and the optimum superheat adjustment range of R32 commercial air conditioning is studied by comparing the system’s parameters of R32 with R22’s under the condition of Case 1,. The experimental results show that: the change trends of the system’s parameters for R32 are similar with that for R22, and the R32 refrigeration system has a higher refrigerating capacity; under the condition of Case 1, the refrigerating capacity and COP of R32 are improved about 42% and 6.8% respectively compared to R22; the system’s pressure ratio is increased about 7%, which indicates R32 system is more stable. At the air-conditioned state, the better energy saving effect can be reached when the superheated degree of R32 system is controlled less than 4℃.